Controlling land use sprawl with geospatial indices for effective local government - Rosni, Nur Aulia; Hj. Mohd. Noor, Norzailawati; Abdullah, Alias (2016)
Controlling the land use sprawl and managing the rapid urban growth process has become key issues for local government agencies in many developing countries including Malaysia. This paper intended to review and examined the core problems of land use sprawl control with local planning policies and the agencies that involve in implementing these processes. Many types of research have been conducted to measure urban sprawling which includes the usage of spatial Indices with GIS and remote sensing techniques. But many of the existing researches has been acknowledging to have left out the local planning policies perspective which creates conflicts of interest with the local government, developers, stakeholders and the community of the particular area. In order to avoid this issues, this paper attempts to review the literature on urban sprawl, the local planning policy and the geospatial indices measurement in order to see the extend of government policies implementation in kerbing urban sprawl growth. Keywords: